The Rise of European Music 1380-1500 - Strohm, Reinhard 1942- (Cambridge Cambridge University Press, 1993)
This is a detailed and comprehensive survey of music in the late middle ages and early Renaissance. By limiting its scope to the 120 years which witnessed perhaps the most dramatic expansion of our musical heritage, the book responds, in the 1990s, to the tremendous increase in specialised research and public awareness of that period. Three of the four main Parts (I, II, IV) describe the development of polyphony and its cultural contexts in many European countries, from the successors of Machaut (d. 1377) to the achievements of Josquin des Prez and his contemporaries working in Renaissance Italy around 1500. Part III, by contrast, illustrates the musical life of the institutions, and musical practices outside the realm of composed polyphony that were traditional and common all over Europe. The book proposes fresh views in each chapter, discussing dozens of musical examples adducing well-known and hitherto unknown documents, and referring to and evaluating the most recent scholarship in the field.
Keywords: Middle Ages (500-1400); Renaissance (1400-1600); Music history; Europe